Early venous manifestation of Ehlers-Danlos syndrome Type IV through a novel mutation in COL3A1 - Wendorff, Heiko; Pelisek, Jaroslav; Zimmermann, Alexander; Mayer, Karin; Seidel, Heide; Weirich, Gregor; Haußer-Siller, Ingrid; Siegel, Corinna; Zernecke, Alma; Eckstein, Hans-Henning (Cardiovascular pathology, 2013)
Ehlers-Danlos syndrome (EDS) leads to abnormalities in the synthesis of collagen and complications involving arterial vessels. We describe here a mutation in the intron 14 of the COL3A1 gene leading to EDS Type IV (EDS IV) associated with venous manifestations only. The patient, an 18-year-old male, suffered from truncal varicosity of the long saphenous vein on both sides. Conventional stripping surgery of the left saphenous vein revealed an extremely vulnerable ectatic superficial femoral vein. An inserted vein graft occluded, and venous thrombectomy was unsuccessful. A conservative anticoagulant and compression therapy finally succeeded. This is the first report describing EDS IV due to a mutation in intron 14 of the COL3A1 gene leading to venous manifestations without affecting arterial vessels at clinical presentation. Our findings imply that molecular genetic analysis should be considered in patients with unusual clinical presentation and that conservative therapy should be applied until a suspected clinical diagnosis has been secured.
Gesehen am 02.11.2021